Innovation, Digital Platform Technologies and Employment: An Overview of Key Issues and Emerging Trends in South Africa - Naidoo, Karmen (Southern Centre for Inequality Studies (SCIS), 2020)
This paper provides an analytical profile of the South African labour market, along with a descriptive overview of the nature and extent of digital platform labour in the country. The paper also discusses the conceptual links between different types of innovation and employment, before reflecting on the implications of new forms of digital labour relations on labour organization and regulation. The literature on South Africa’s digital platform labour is nascent. Some estimates suggest that there are about 135 000 platform workers in the country. There are, however, important concerns about the quality of platform work, and recent research suggests that many platforms do not provide workers with a living wage or decent working conditions. There are several challenges to regulating platform work, in part due to workers being classified as independent contractors. Despite this, there are new emerging forms of worker organization amongst precarious workers in South Africa that go beyond traditional trade unions to incorporate broader worker associations.
Keywords: Future of workers; South African labour market; Digital platform labour; Innovation and employment; Digital labour relations; Labour organization and regulation